2021
DOI: 10.4018/ijssmet.290331
|View full text |Cite
|
Sign up to set email alerts
|

Service Excellence in Marketing for Firms

Abstract: Innovation and differentiation are imperative for companies to sustain in the competition. Innovation and differentiation are possible more in services than in physical products. It is difficult to imitate differentiation incorporated in services. The study discusses the various marketing strategies adopted by service companies and the roles played by service profit chain. Service companies adopt different initiatives to achieve excellence. These include a strategic orientation, commitment from the top managem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…This study sheds light on the importance of maintaining excellence in offering services to customers, in line with several existing studies. For example, Mandal (2022) indicated the importance of providing excellent services through continual innovation strategies and initiatives, affecting service quality and productivity. Windasari & Lin (2021) highlighted the importance of sustainable innovation practices in serving customers.…”
Section: Discussionmentioning
confidence: 99%
“…This study sheds light on the importance of maintaining excellence in offering services to customers, in line with several existing studies. For example, Mandal (2022) indicated the importance of providing excellent services through continual innovation strategies and initiatives, affecting service quality and productivity. Windasari & Lin (2021) highlighted the importance of sustainable innovation practices in serving customers.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, customers are satisfied or delighted when the perceived service is more than the expected service (Rahmatulloh & Melinda, 2021). Successful companies aim to add benefits to their offerings that not only satisfy customers but also surprise and delight them by exceeding expectations (Mandal, 2022). Many companies like American Express and SBI YONO from India develop their businesses around exceeding customer expectations.…”
Section: Management Of Customer Expectationsmentioning
confidence: 99%
“…The analysis of theoretical sources has revealed that AI technologies have transformed the landscape of retail trade, enriching reality through the interaction of consumers and retailers via online interfaces (Kautish & Khare, 2022). This has been aimed at achieving excellence amidst uncertainty and competitive struggle (Mandal, 2022). Nowadays, the analysis of theoretical sources has shown that the popularity of AI topics in the scientific literature may soon surpass the popularity of this topic among science-fiction writers.…”
Section: Literature Reviewmentioning
confidence: 99%